Year of Health and Care Workers 2021 - Center of Excellence of Healthcare; Pharmacy Specialists informs (Slauga. Mokslas ir praktika, 2021)
2021 has been designated as the International Year of Health and Care Workers in appreciation and gratitude for their unwavering dedication in the fight against the COVID-19 pandemic. WHO is launching a year-long campaign, under the theme – Protect. Invest. Together. It highlights the urgent need to invest in health workers for shared dividends in health, jobs, economic opportunity and equity.